Internal Forces Tests in Retaining Walls of Road Embankments - Surowiecki, Andrzej; Hutnik, Edward (Communications - Scientific letters of the University of Zilina, 2003)
The subjects of this paper are resistance structures constituted by reinforced soil applied in highway engineering. Test results carried out on laboratory models are presented, leading to the estimation of the size and shape of the wedge of the reinforced soil embankment block, in the boundary state of active pressure. The task was conducted in the following two stages: on the basis of measured horizontal strains of the embankment (unitary lateral pressures) and reinforcing dowels - with the application of sensors of electro-resistant tensometry. The slip curve, determining the searched block wedge, is formed by the points of maximal normal stress occurring in the reinforcement dowels located in the horizontal layers. The slip curve divides the embankment area into two zones: active (block wedge) and passive, in which dowel anchorage takes place.